2018
DOI: 10.1097/md.0000000000009767
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical characteristics and treatment of immunoglobulin G4-associated cholangitis

Abstract: Immunoglobulin (Ig)G4-associated cholangitis (IAC) is one of the common organ manifestations of IgG4-related systemic disease (ISD). IAC and autoimmune pancreatitis (AIP) may mimic sclerosing cholangitis, cholangiocarcinoma, or pancreatic carcinoma. Diagnosis is based on a combination of clinical, biochemical, radiological, and histological findings.To study the clinical presentation of and treatment strategy for IAC, we reviewed clinical, serologic, and imaging characteristics, as well as treatment response, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
7
0
2
Order By: Relevance
“…Two prospective studies 84 , 85 , six retrospective, observational cohort studies (>20 patients each), 73 , 78 , 86–89 and one systematic review 90 evaluating the response to glucocorticoids have been considered for analysis; different studies have been excluded, as these were non‐randomized and with less than 20 patients enrolled. These studies 73 , 78 , 84–90 showed differences in inclusion criteria and bile duct involvement, definition of response (clinical, biochemical, radiologic), type of glucocorticoids, doses and length of treatment, modalities of tapering, and additional treatments (surgery, stenting). Nonetheless, these studies demonstrated a rate of response from 62 to 100% with a relapse of approximately 30% during glucocorticoid tapering or after withdrawal of glucocorticoids.…”
Section: Introduction and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Two prospective studies 84 , 85 , six retrospective, observational cohort studies (>20 patients each), 73 , 78 , 86–89 and one systematic review 90 evaluating the response to glucocorticoids have been considered for analysis; different studies have been excluded, as these were non‐randomized and with less than 20 patients enrolled. These studies 73 , 78 , 84–90 showed differences in inclusion criteria and bile duct involvement, definition of response (clinical, biochemical, radiologic), type of glucocorticoids, doses and length of treatment, modalities of tapering, and additional treatments (surgery, stenting). Nonetheless, these studies demonstrated a rate of response from 62 to 100% with a relapse of approximately 30% during glucocorticoid tapering or after withdrawal of glucocorticoids.…”
Section: Introduction and Methodologymentioning
confidence: 99%
“…No randomized controlled study on the short-term treatment of IRC has been performed and no randomized controlled trial has been performed testing glucocorticoid-response as a criterion for the diagnosis of IRC. Two prospective studies 84,85 , six retrospective, observational cohort studies (>20 patients each), 73,78,[86][87][88][89] and one systematic review 90 evaluating the response to glucocorticoids have been considered for analysis; different studies have been excluded, as these were non-randomized and with less than 20 patients enrolled. These studies 73,78,[84][85][86][87][88][89][90] showed differences in inclusion criteria and bile duct involvement, definition of response (clinical, biochemical, radiologic), type of glucocorticoids, doses and length of treatment, modalities of tapering, and additional treatments (surgery, stenting).…”
Section: Q22: What Are the Imaging Features Of Aip? Statement 22mentioning
confidence: 99%
“…In this case, prednisolone was used, but resection was not performed. The patient’s symptoms improved, but the number of IgG4-positive cells did not change after remission [13].…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that operation is one of the feasible tactics of treatment of IgG4-RD in a particular situation, such as in a case we are reluctant to use steroid (e.g., a patient with diabetes mellitus). Xiao et al reported that among 39 cases of IgG4-related cholangitis, 4 underwent surgery [13]. Among these 4 cases, 2 underwent pancreatoduodenectomy, 1 underwent choledochojejunostomy, and the fourth one underwent choledochoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Two prospective studies 84,85 , six retrospective, observational cohort studies (>20 patients each), 73,78,[86][87][88][89] and one systematic review 90 evaluating the response to glucocorticoids have been considered for analysis; different studies have been excluded, as these were non-randomized and with less than 20 patients enrolled. These studies 73,78,[84][85][86][87][88][89][90] showed differences in inclusion criteria and bile duct involvement, definition of response (clinical, biochemical, radiologic), type of glucocorticoids, doses and length of treatment, modalities of tapering, and additional treatments (surgery, stenting). Nonetheless, these studies demonstrated a rate of response from 62 to 100% with a relapse of approximately 30% during glucocorticoid tapering or after withdrawal of glucocorticoids.…”
Section: Overviewmentioning
confidence: 99%